THE INFLUENCE OF CHOPPED COPPER FIBRE (CF) ON THE IMPROVEMENT OF PURE GYPSUM BY COMPRESSIVE STRENGTH - AL-Ridha, Ahmed S.D; Abbas, Firas Saeed; Faris, Hamid Abdul Mahdi; Dheyab, Layth Sahib; Ali, Eng. Hameed Zaier; Mohialdeen, Eng. Mohammed Sabah (Journal of Applied Engineering Science, 2022)
This study investigates the efficacy, performance, and effect of chopped Copper Fibre (CF) on a Pure Gypsum (PG) mixture. The Copper Fibre (CF) is extracted from the waste of electrical wires that are considered as environmental waste. Three models of Copper Fibre (CF) with a diameter of 0.83 (mm) and lengths of 10 (mm), 20 (mm), and 30 (mm) (Aspect-Ratio L/d = 12, 24 and 36 respectively), with Volume Fraction (V.f.) for Copper Fibre (CF) by two Water/Gypsum Ratios (W/G) worth (0.5 and 0.6) are created. The mixtures are divided into two groups of W/G ratios. Each group contains four samples, one reference without Copper Fibre (CF) and the other three with the addition of Copper Fibre (CF) individually with different lengths. The results show that adding Copper Fibre (CF) to the Pure Gypsum (PG) mixture increases the Compressive Strength. Further, the effect is to heighten the Compressive Strength of Pure Gypsum (PG) when the Aspect-Ratio is raised. In other words, when the (W/G) Ratio is reduced, the Compressive Strength increases in the presence or absence of Copper Fibre (CF). Moreover, the efficiency of the Copper Fibre (CF) develops further when the W/G ratio is decreased.
Keywords: environmental waste, copper fibre (CF), pure gypsum (PG), (L/d) asspect-ratio, compressive strength, volume-fraction of CF (V.f.)